2007
DOI: 10.11646/zootaxa.1636.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Eucnemidae (Coleoptera) of the Maritime Provinces of Canada: new records, observations on composition and zoogeography, and comments on the rarity of saproxylic beetles

Abstract: The Family Eucnemidae in the Maritime Provinces of Canada is surveyed. Eleven species are now known from the region. Ten species are recorded in Nova Scotia, six in New Brunswick, and four on Prince Edward Island. Nine new provincial records (four from Nova Scotia, four from Prince Edward Island, and one from New Brunswick) are reported, and two species, Microrhagus triangularis (Say) and Nematodes penetrans (LeConte), are newly recorded in the Maritime Provinces as a whole. The four species reported from Prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…If the goal in managing forests in Nova Scotia is to maintain patterns of heterogeneity similar to those that arise after natural disturbances, the indication off ered here by saproxylic beetles is that this goal is not being met. Majka (2007) examined 14 families, subfamilies, and tribes of saproxylic beetles in the Maritime Provinces of Canada and found 59 apparently rare species (representing ≤ 0.005% of specimens from the region) that comprise 33% of the 178 species within these groups. Majka (2007) proposed that this apparent scarcity of a large proportion of the saproxylic fauna might be due to the history of forest management practices in the region.…”
Section: Alpha Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…If the goal in managing forests in Nova Scotia is to maintain patterns of heterogeneity similar to those that arise after natural disturbances, the indication off ered here by saproxylic beetles is that this goal is not being met. Majka (2007) examined 14 families, subfamilies, and tribes of saproxylic beetles in the Maritime Provinces of Canada and found 59 apparently rare species (representing ≤ 0.005% of specimens from the region) that comprise 33% of the 178 species within these groups. Majka (2007) proposed that this apparent scarcity of a large proportion of the saproxylic fauna might be due to the history of forest management practices in the region.…”
Section: Alpha Diversitymentioning
confidence: 99%
“…Majka (2007) examined 14 families, subfamilies, and tribes of saproxylic beetles in the Maritime Provinces of Canada and found 59 apparently rare species (representing ≤ 0.005% of specimens from the region) that comprise 33% of the 178 species within these groups. Majka (2007) proposed that this apparent scarcity of a large proportion of the saproxylic fauna might be due to the history of forest management practices in the region. If Nova Scotia has not yet suff ered biodepletion to the extent of European forests, this may only refl ect the fact that not enough time has passed for the deadwood lingering from old-forests in second-growth forests to fully return to soil.…”
Section: Alpha Diversitymentioning
confidence: 99%
“…For instance only two species (14% of the native fauna) have been recorded on PEI, and only one species (7%) on Cape Breton Island. Majka (2007b) surveying 18 families, subfamilies, and tribes of native saproxylic beetles (a total of 283 species) in the Maritime Provinces found that the Prince Edward Island fauna (85 species) was comprised of 30% of the total mainland fauna while the Cape Breton Island fauna (94) species was 33% of the total mainland fauna. On this basis it would appear that the ciid fauna of both these islands should include additional, as yet undocumented species.…”
Section: Distribution Of the Ciid Faunamentioning
confidence: 99%
“…Apparently Rare Species Majka (2007b) summarized information on the abundance of saproxylic beetles in 18 families, subfamilies, and tribes in the Maritime Provinces of Canada, drawing attention to the fact that 59 of 283 species (20.8%) were apparently rare ("rare" defined as representing < 0.005% of specimens examined from the region). Based on that criterion, Cis horridulus, Cis striolatus, and Cis subtilis, are very infrequently collected (< 5 specimens out of a total of 100,000 Coleoptera specimens examined), and would be considered apparently rare.…”
Section: Fungal Host Groups and Ciid Faunal Compositionmentioning
confidence: 99%
“…Majka examined various regional collections, including the NBM, UMC, CNC, and many other collections and published a series of papers between 2005 and 2011, reviewing the Coleoptera fauna of the Maritime Provinces, which included numerous new records from New Brunswick. Majka and various coauthors treated 61 families (listed in taxonomic order) in the following publications, adding 259 new records for New Brunswick, including eight new Canadian records, and one new North American record [number of new provincial records (NPR) or new Canadian records (NCR) in brackets]: Gyrinidae [4 NPR] (Majka and Kenner 2009), Carabidae [6 NPR] (Majka et al 2007c), Haliplidae [6 NPR] (Majka et al 2009d), Histeridae [2 NPR] (Majka 2008a), Ptiliidae [5 NPR including 1 NCR] (Majka and Sörensson 2007), Leiodidae [8 NPR] (Majka and Langor 2008), Lucanidae [3 NPR] (Majka 2008c), Eucinetidae [1 NPR] (Majka 2010a), Clambidae [2 NPR] Majka and Langor 2009), Byrrhidae [4 NPR] (Majka et al 2007d, Majka and Langor 2011b), Eucnemidae [1 NPR] (Majka 2007c), Throscidae (Majka 2011b), Elateridae [13 NPR] (Majka and Johnson 2008), Derodontidae, Dermestidae [3 NPR], Bostrichidae [1 NPR], Ptinidae [3 NPR] (Majka 2007b), Trogossitidae [3 NPR] (Majka 2011c), Cleridae [3 NPR] (Majka 2006b), Melyridae [3 NPR] (Majka 2005), Sphindidae [2 NPR] (Majka 2010b), Erotylidae [2 NPR] (Majka 2007a, Majka et al 2010c), Monotomidae [1 NPR] (Majka and Bousquet 2010), Cryptophagidae [9 NPR including 1 NCR] (Majka et al 2010a, Majka and Langor 2010), Silvanidae [2 NPR], Cucujidae ...…”
mentioning
confidence: 99%